Self-Care Strategies and Job Satisfaction in Pediatricians: What We Can Do to Prevent Burnout-Results of a Nationwide Survey - Ulrike Leiss; Ulrike Leiss; Andrea Schiller; Jonathan Fries; Jonathan Fries; Jonathan Fries; Peter Voitl; Andreas Peyrl; Andreas Peyrl (Frontiers Media S.A., 2021)
Introduction: Working in the clinical field can be a demanding experience. While reports indicate escalating burnout rates among physicians, further investigation about what physicians can do to prevent burnout is necessary. Our objective was to assess self-care levels among pediatricians and the correlation with job satisfaction in order to subsequently identify protective factors.Methods: In this nationwide, cross-sectional study, a web-based survey was distributed to all Austrian pediatricians via a mailing list of the Austrian Society of Pediatrics. Self-care was measured with a modified Professional Self-Care Scale (PSCS), which consisted of nine items on a four-point Likert scale (from 1, "totally disagree," to 4, "totally agree"). Additional items addressed job satisfaction, peer support, and access to professional coaching.Results: The survey was distributed to 1,450 mailing list contacts, a total of 309 Austrian pediatricians completed the survey (21%). "Family" (M = 3.3) and "Friends" (M = 3.1) were the most highly rated self-care strategies. We found significant differences between pediatricians under 35 years and those aged 50 years and above (z = −4.21, p < 0.001). Peer support appeared to impact job satisfaction substantially. We found differences between pediatricians who frequently talk to colleagues about difficult situations, those who sometimes do so, and those who never do (p < 0.001), with a linear trend indicating increased job satisfaction with more frequent peer support (p < 0.001).Conclusions: Among all self-care strategies, a stable network of family and friends was highest rated, followed by balanced nutrition. Younger, male pediatricians working in hospital showed to be a vulnerable group with regard to overall self-care. Moreover, higher self-care values were found among those pediatricians who reported to receive peer support on a regular basis. We suggest combined organizational and individual interventions to promote pediatricians' well-being. Organizations should provide the possibility to select a well-balanced diet as well as space and time to consume food and cultivate a work environment that enables communication among peers and facilitates professional coaching. On the personal level, we want to encourage pediatricians to talk to trusted colleagues in challenging clinical situations and to consider working with a professional coach.